Surgical Chin Reduction: Achieving a Balanced Result - Sykes, Jonathan; Mehrdad, Madison (Facial Plastic Surgery, 2025)
The chin plays a critical role in establishing facial balance and proportions. Abnormalities of chin projection, height, width, and symmetry can affect perioral aesthetics, gender alignment, and aging.Patients who present for aesthetic perioral enhancement should have a complete evaluation of the perioral bony anatomy. Chin excess may occur in the horizontal, vertical, and transverse dimensions. Surgical chin contouring may require both deprojection and shortening.The technique for both horizontal and vertical chin reduction will be reviewed in addition to complications.The chin is a critical component of facial harmony and should be evaluated and addressed during aesthetic enhancement and rejuvenation.
Keywords: chin reduction; macrogenia; surgical techniques; chin contouring